Kristus sebagai Juruselamat dalam Perspektif Soteriologi Kristen: Relasi Anugerah, Iman, dan Keselamatan di Tengah Krisis Spiritualitas Modern - Rendy Herwindo Wibisono (KAPATA: Jurnal Teologi dan Pendidikan Kristen, 2025)
This study examines Jesus Christ as the only Savior of humanity from the perspective of Christian soteriology by emphasizing the relationship between grace, faith, and Christ’s salvific work. The background of this research is rooted in the rise of religious relativism and the crisis of modern spirituality, which tend to reduce the meaning of Christian salvation to merely moral achievement and subjective spiritual experience. This study aims to analyze the sinful condition of humanity, the person and work of Jesus Christ, the concept of salvation by grace, and humanity’s response of faith toward God’s saving work. The research employs a qualitative method with a library research approach through biblical and theological analysis of Scripture, theological books, and relevant scholarly journals. The findings reveal that fallen humanity is incapable of saving itself and therefore requires a perfect Savior, namely Jesus Christ as fully God and fully human. Salvation is granted solely by the grace of God through Christ’s redemptive work on the cross and is received through faith in Him. Christ’s resurrection becomes the assurance of victory over sin and death as well as the foundation of eternal hope for believers. This study affirms that Christian salvation is Christ-centered and exclusive, making it highly relevant for strengthening the faith foundation of the church amid the challenges of pluralism and modern spiritual relativism.